Editorial: Bioengineering for a better quality of life. Issue 8 (10th August 2015) - Ferreira, Guilherme; Jacques, Philippe
<x xml:space="preserve">Abstract</x> With an ever growing population demanding of more food and a better quality of life, the current and future demands of mankind are centered to provide products and technologies which are enabling more efficient energy production, clean water and air, active aging, and increased food quantity, security and quality.